2015
DOI: 10.1016/j.neuroscience.2015.06.033
|View full text |Cite
|
Sign up to set email alerts
|

The ins and outs of the striatum: Role in drug addiction

Abstract: Addiction is a chronic relapsing disorder characterized by the loss of control over drug intake, high motivation to obtain drug, and a persistent craving for the drug. Accumulating evidence implicates cellular and molecular alterations within cortico-basal ganglia-thalamic circuitry in the development and persistence of this disease. The striatum is a heterogeneous structure that sits at the interface of this circuit, receiving input from a variety of brain regions (e.g., prefrontal cortex, ventral tegmental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
249
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(273 citation statements)
references
References 157 publications
(193 reference statements)
9
249
0
Order By: Relevance
“…It was also revealed that aripiprazole may act as a potent partial agonist, weak agonist, or antagonist depending upon the cellular environments of the targeted D 2 receptors (Burris et al, 2002, Kikuchi et al, 1995, Lawler et al, 1999, Mailman and Murthy, 2010, Shapiro et al, 2003, Urban et al, 2007. It should be noted that the NAc and CPu are heterogeneous structures with different connections with various brain regions (reviewed by Yager et al, 2015). For example, the NAc receives dopaminergic inputs from the ventral tegmental area (VTA) and links with limbic areas and the PFC, while the CPu receives dopaminergic inputs from the substantia nigra pars (SN) and links with neocortical areas, particularly the motor areas (Yager et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also revealed that aripiprazole may act as a potent partial agonist, weak agonist, or antagonist depending upon the cellular environments of the targeted D 2 receptors (Burris et al, 2002, Kikuchi et al, 1995, Lawler et al, 1999, Mailman and Murthy, 2010, Shapiro et al, 2003, Urban et al, 2007. It should be noted that the NAc and CPu are heterogeneous structures with different connections with various brain regions (reviewed by Yager et al, 2015). For example, the NAc receives dopaminergic inputs from the ventral tegmental area (VTA) and links with limbic areas and the PFC, while the CPu receives dopaminergic inputs from the substantia nigra pars (SN) and links with neocortical areas, particularly the motor areas (Yager et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the NAc and CPu are heterogeneous structures with different connections with various brain regions (reviewed by Yager et al, 2015). For example, the NAc receives dopaminergic inputs from the ventral tegmental area (VTA) and links with limbic areas and the PFC, while the CPu receives dopaminergic inputs from the substantia nigra pars (SN) and links with neocortical areas, particularly the motor areas (Yager et al, 2015). Blockade of dopamine D 2 receptor activity in the mesolimbic (VTA-NAc) pathway is the common mechanism of antipsychotic actions, particularly in the control of positive symptoms of schizophrenia (Ginovart and Kapur, 2012); in addition, EPS side-effects induced by antipsychotics are related to the blockade of D 2 receptors in the nigrostriatal (SN-CPu)…”
Section: Discussionmentioning
confidence: 99%
“…Other neuromodulators and neurotransmitters may also contribute to the BOLD response in the striatum, such as acetylcholine, GABA, or glutamate (Knudsen 2011;Stormer et al 2012;Yager et al 2015). However, transient modulations of fMRI signal across the mesolimbic DA system during reward processing has previously been demonstrated to be highly consistent with neural recordings in animals (Schultz et al 1997;Knutson et al 2001aKnutson et al , 2001bTobler et al 2005;D'Ardenne et al 2008;Ferenczi et al 2016).…”
Section: Hemispheric Reward Asymmetry and Hemispheric Asymmetries Inmentioning
confidence: 99%
“…However, DA-mediated appetitive motivation drives behaviors that are not always under goal-directed control and can be maladaptive (Aarts et al, 2011), as occurs in drug addiction (Bustamante et al, 2013;Everitt & Robbins, 2013;Fowler et al, 2007;Garavan & Hester, 2007;Garavan & Weierstall, 2012;Goldstein et al, 2009c;Moeller et al, 2012;Nutt et al, 2015;Yager et al, 2015). Specifically, the improper DA modulation of the PFC via frontostriatal connections (Bustamante et al, 2012;Volkow et al, 2012;Yager et al, 2015) implies PFC dysfunction and the user's loss of control over the drug craving (Goldstein & Volkow, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, DA-mediated appetitive motivation drives behaviors that are not always under goal-directed control and can be maladaptive (Aarts et al, 2011), as occurs in drug addiction (Bustamante et al, 2013;Everitt & Robbins, 2013;Fowler et al, 2007;Garavan & Hester, 2007;Garavan & Weierstall, 2012;Goldstein et al, 2009c;Moeller et al, 2012;Nutt et al, 2015;Yager et al, 2015). Specifically, the improper DA modulation of the PFC via frontostriatal connections (Bustamante et al, 2012;Volkow et al, 2012;Yager et al, 2015) implies PFC dysfunction and the user's loss of control over the drug craving (Goldstein & Volkow, 2011). This craving is characterized by great salience and brain reactivity to cocaine-related stimuli at the expense of other appetitive stimuli (Dunning et al, 2011;Garavan et al, 2000;Wilcox, Teshiba, Merideth, Ling, & Mayer, 2011), and it is considered a sign of addiction severity in drug users (Colzato et al, 2007;Garavan et al, 2000;Jasinska et al, 2014;Modesto-Lowe et al, 1997).…”
Section: Introductionmentioning
confidence: 99%